2010
DOI: 10.1002/jsfa.4214
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Lactobacillus fermentum SM-7 isolated from koumiss, a potential probiotic bacterium with cholesterol-lowering effects

Abstract: The results suggested that L. fermentum SM-7 is a potential probiotic bacterium with cholesterol-lowering effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 34 publications
3
64
0
3
Order By: Relevance
“…In mice, L. fermentum SM-7 significantly reduced serum TC and LDL-C but did not increase HDL-C significantly [6]. The study also showed that there was no bacterial translocation in the liver, spleen, or kidney of the treated mice indicating safety of the Lactobacillus strain [6].…”
Section: Hypocholesterolaemic Effects Of Probioticsmentioning
confidence: 78%
See 4 more Smart Citations
“…In mice, L. fermentum SM-7 significantly reduced serum TC and LDL-C but did not increase HDL-C significantly [6]. The study also showed that there was no bacterial translocation in the liver, spleen, or kidney of the treated mice indicating safety of the Lactobacillus strain [6].…”
Section: Hypocholesterolaemic Effects Of Probioticsmentioning
confidence: 78%
“…Kumar et al [67] revealed a 23% reduction in plasma TC, 38% reduction in LDL-C and 19% increase in HDL-C of rats fed with L. plantarum Lp91, a bile salt hydrolase producing strain. The faecal excretion of cholic acid was also found to be significantly higher in the probiotic-fed rats [6].…”
Section: Hypocholesterolaemic Effects Of Probioticsmentioning
confidence: 84%
See 3 more Smart Citations